2007
DOI: 10.2320/matertrans.48.610
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Microstructure and Electrical Conductivity of Amorphous AgInSbTe and SbTe Films during Crystallization

Abstract: Two kinds of chalcogenide films with similar Sb/Te atomic ratios, AgInSbTe (AIST) and SbTe (ST) were deposited on alkali-free glass using the RF sputtering method. The microstructure characteristics of both ST and AIST films were demonstrated to correlate with the electrical properties. TEM observation and GI-XRD profiles revealed that the structures of as-deposited AIST and ST films were amorphous characteristics. The sheet resistance of the as-deposited AIST films was twice as high as that of ST films and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, the crystallization properties and structural changes in pure and Ge-doped Sb 70 Te 30 eutectic films are not fully understood so far. For example, the values reported in the literature for the activation energy for crystallization of amorphous Sb 70 Te 30 films varied in a wide range, 0.84 [9], 1.3 [10] and 2.9 [11] eV. In ref [10] it has been reported that undoped and Ge-doped Sb 70 Te 30 films (with 1.6, 5.7 and 9% of Ge) have the same Sb rhombohedral structure and according to ref.…”
Section: Introductionmentioning
confidence: 92%
“…However, the crystallization properties and structural changes in pure and Ge-doped Sb 70 Te 30 eutectic films are not fully understood so far. For example, the values reported in the literature for the activation energy for crystallization of amorphous Sb 70 Te 30 films varied in a wide range, 0.84 [9], 1.3 [10] and 2.9 [11] eV. In ref [10] it has been reported that undoped and Ge-doped Sb 70 Te 30 films (with 1.6, 5.7 and 9% of Ge) have the same Sb rhombohedral structure and according to ref.…”
Section: Introductionmentioning
confidence: 92%
“…According to previous studies, 24,25) the semi-crystallized films also possess electrical properties and can act as fullycrystallized films. For applications using TCO film with copolymer substrates, the potential of the present electrical current crystallization method seems enormous.…”
Section: Crystallization and Raman Characteristicsmentioning
confidence: 99%
“…The main reason is that the number of lithium ions inserted was similar. However, the area of passive film for SC1500-H increased due to the growth of thermal cracks, 28) which caused the insertion of lithium ions to be inhibited and the cycleability to deteriorate (Fig. 10).…”
Section: Recrystallized Behavior and Compound Phasesmentioning
confidence: 99%
“…According to a reference, 28,29) the IOC and resistivity have an inverse tendency. The IOC and resistivity of each film are shown in Table 2, which reveals that the SC1500-H film had a higher IOC and lower resistivity.…”
Section: Recrystallized Behavior and Compound Phasesmentioning
confidence: 99%